Hope and its relationship to motivation for achievement for a sample of high school students in Al-Qunfudhah - Alsayed, Mohammed Ahmed Shbeir; Alhasani, Ibraheem Abutaleb Mohammed; Nasr, Fathy Mahdy Mohamed (Journal of Educational and Psychological Sciences, 2021)
The research aimed to identify the relationship between hope and motivation for achievement among a sample of high school students in Al-Qunfudah Governorate, and to verify the presence of differences attributable to the variable of the school year (first year, second year, third year), and the variable of academic specialization (scientific and literary) on the degrees of the individuals of the research sample in hope and motivation for achievement. The total research sample consisted of (303) students in the high school in Al-Qunfudah Governorate, randomly chosen, average ages 14-17 years. The researcher used the hope scale (researcher preparation) and the achievement motivation scale (researcher preparation), and the researcher used the relational descriptive approach due to its suitability of the nature of the research problem and its goals. The results of the study resulted in: The presence of a relationship between the total score of the measure of hope and the total score of the scale of achievement motivation where the correlation coefficient reached (0.730). The presence of a positive, statistically significant correlation between the scores of the research sample individuals on the hope scale and their scores on the achievement motivation scale as follows: The first perspective "Positive meaning of life" from the scale of hope with dimensions of the achievement motivation scale (ability to persevere, clarity of purpose, level of ambition, efficiency and independence, ability to challenge, and the overall degree of the scale of achievement motivation), the second perspective "positive outlook for the future" from the measure of hope with dimensions of the achievement motivation scale (ability to persevere, clarity of purpose, level of ambition, efficiency and independence, ability to challenge, and the overall degree of the scale of achievement motivation), the third perspective "the force of personal will" from the measure of hope with the dimensions of the achievement motivation scale (ability to persevere, clarity of purpose, level of ambition, efficiency and independence, ability to challenge, and the overall degree of the scale of achievement motivation), among the most important recommendations reached by the study: Training students on how to build hope within themselves through positive training with the aim of increasing their motivation for achievement, working to develop achievement motivation among male and female students at different educational levels, training students in the early stages of education - the primary stage - to adopt methods that inspire hope in their future perceptions and encourage them on an ongoing basis, provide training programs to develop hope and improve motivation achievement for high school students, providing provide advisory programs to increase the awareness of high school students about the role of hope and its importance in an individual’s life.